Vaccination Uptake and Pandemic-Related Healthcare Experiences Among People Living with HIV in Romania: A Cross-Sectional Study - Adrian Gabriel Marinescu; Aida-Isabela Adamescu; Cătălin Tilișcan; Daniela Pițigoi; Sebastian Ciobanu; Laurențiu Mihăița Stratan; Carmen Cristina Vasile; Victor Daniel Miron; Mariana Mardarescu; Dalila Toma; Andreea Iuliana Ciobanu; Victoria Aramă; et al. (Vaccines, 2026)
Background: The COVID-19 pandemic exposed major vulnerabilities in healthcare accessibility and may have influenced preventive attitudes among people living with HIV (PLWH). However, the relationship between pandemic-related healthcare experiences and vaccination uptake remains insufficiently understood. Materials: A cross-sectional survey was conducted among 203 adults living with HIV receiving follow-up care in Romania between October 2025 and March 2026. The questionnaire evaluated vaccination uptake, vaccine-related perceptions, healthcare information sources, and pandemic-related experiences. Multivariable logistic regression analysis was performed to identify factors independently associated with vaccination uptake. Results: Only 38.9% of participants reported receiving at least one vaccine within the previous three years. The main barriers to vaccination were perceived lack of necessity, lack of physician recommendation, fear of adverse effects, and lack of trust. Multivariable logistic regression identified positive vaccine-related beliefs (OR = 0.454, 95% CI: 0.235–0.876, p = 0.019) and CD4+ T-cell count above 500 cells/mm3 (OR = 0.448, 95% CI: 0.232–0.867, p = 0.017) as independently associated with lower odds of being non-vaccinated. More than half of participants (52.7%) reported at least one pandemic-related disruption or negative health impact. The pandemic-related negative impact composite was not significantly associated with vaccination status (p = 0.209), whereas confirmed COVID-19 infection was more frequent among vaccinated participants than among non-vaccinated participants (43.0% vs. 28.2%, p = 0.030). Pandemic-related negative impact was associated with a greater demand for physician-provided information (p = 0.011). Conclusions: Pandemic-related healthcare experiences were associated with greater demand for physician-provided preventive information, while confirmed COVID-19 infection was more frequent among vaccinated participants. Positive vaccine-related beliefs and higher CD4+ T-cell counts were independently associated with vaccination uptake, while lack of physician recommendation remained a major barrier to vaccination. These findings emphasize the critical role of physicians in improving vaccination coverage among people living with HIV in the post-pandemic era.